How Can Social Workers Assess Clinically Meaningful Change in Their Clients? An Example from Children in Care. - Baviskar, Siddhartha; Bergström, Martin (Clinical Social Work Journal, 2023)
Social workers use interventions in the expectation that they will make a positive difference for their clients. However, research about the effectiveness of interventions is typically presented at the group level, which places great demands on social workers' ability to apply such results to the needs of individual clients. Further, the content and effects of "service as usual" (SAU) interventions that social workers typically offer are often not known, making it difficult for social workers to identify what aspects of the intervention any client change can be attributed to. Using indicators of clinically meaningful change (CMC) strengthens social workers' ability to identify what, if anything, works in any given intervention for their individual clients, and also motivates their curiosity to identify the efficacious components of SAU. CMC refers to changes in an individual's outcome measures that are reliable or are large enough to be considered "important." We present five indicators to analyze CMC in a child's psychological well-being measured with the Strengths and Difficulties Questionnaire and illustrate their use with two empirical examples from the project Me and My Foster Family. The examples demonstrated that conclusions regarding CMC can vary depending on the indicator used, the baseline assessment, and the magnitude of raw-score change on the measured outcome. To assess change at the individual level it is important to address questions of measurement reliability and the yardstick for judging when a change is large enough to be considered "important." Implications for research and practice are discussed.